Identifikasi dan Uji Penangkapan Radikal 2,2 Difenil-1-Pkrilhidrazil (DPPH) dari Ekstrak Kasar Pigmen Bakteri Simbion Rumput Laut - Tien Nova Yenusi; Popy Ida L Ayer; Iriani Ira Bukorpioper; Jotje A Ingratubun; Albida Rante Tasak (Universitas Teuku Umar, 2023)
Abstrak Seaweed belongs to the group of natural antioxidants, these antioxidants are able to counteract free radicals. Secondary metabolites that are antioxidants include alkaloids, flavonoids, phenolic compounds, steroids, and terpenoids and carotenoids. This study aims to identify and test the radical scavenging of 2,2 diphenyl-1-pkrylhydrazyl (DPPH) from the crude extract of the macroalgae symbiont pigment Turbinaria conoides originating from the coastal waters of Hamadi Jayapura, Papua. The method used in this study is an experimental method by identifying pigments using Thin Chromatography (TLC), and for Antioxidant testing using the DPPH Method. The results of the study used the TLC plate Spot 1 on the yellow TLC plate, which had a Retardation frequency (Rf) value of 5/8 = 0.62 and was identified as a carotenoid. The pigment extract of the TC.11 symbiont bacterial pigment extract also has antioxidant potential which was tested by the DPPH method. See the IC50 value of TC.11 bacteria of 24315 ppm compared to the β-carotene marker of 4103 ppm